The answer to this problem is x 3 − 2 1 x 2 + 1 4 8 x − 3 4 3 , where x is the answer to this problem.
What is the answer?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 3 − 2 1 x 2 + 1 4 8 x − 3 4 3 = x ⟹ x 3 − 2 1 x 2 + 1 4 7 x − 3 4 3 = 0 . Now assume f ( x ) = x 3 − 2 1 x 2 + 1 4 7 x − 3 4 3 = 0 .
f ( x ) ⇒ x 3 − 2 1 x 2 + 1 4 7 x − 3 4 3 ⇒ x 3 − 7 x 2 − 1 4 x 2 + 9 8 x + 4 9 x − 3 4 3 ⇒ x 2 ( x − 7 ) − 1 4 x ( x − 7 ) + 4 9 ( x − 7 ) ⇒ ( x − 7 ) ( x 2 − 1 4 x + 4 9 ) ⇒ ( x − 7 ) ( x − 7 ) 2 ⇒ ( x − 7 ) 3 ⇒ x − 7 ⟹ x = 0 = 0 = 0 = 0 [ Since f(7) = 0, x - 7 is a factor of f(x) ] = 0 = 0 = 0 = 0 = 7
Relevant wiki: Rational Root Theorem - Basic
x 3 − 2 1 x 2 + 1 4 8 x − 3 4 3 x 3 − 2 1 x 2 + 1 4 7 x − 3 4 3 x 3 − 3 ( 7 ) x 2 + 3 ( 7 2 ) x − 7 3 ( x − 7 ) 3 x = x = 0 = 0 = 0 = 7 As given By rational root theorem and noting that 3 4 3 = 7 3 The only real solution
Problem Loading...
Note Loading...
Set Loading...
Set x 3 − 2 1 x 2 + 1 4 8 x − 3 4 3 equal to x because they are both the answer to this problem and are therefore equal. Subtracting x from both sides yields x 3 − 2 1 x 2 + 1 4 7 x − 3 4 3 = 0 , which is the same as ( x − 7 ) 3 = 0 . Thus, the answer is 7 .